OPTIMIZATION OF FLEET UTILIZATION AND WAITING TIME IN SUPPLY CHAIN AGENT-BASED SIMULATION USING REINFORCEMENT LEARNING - Tama, Ishardita Pambudi; Sujarwo, Sujarwo; Hardiningtyas, Dewi; Nugroho, Willy Satrio; Salsabila, Dhia Naqqiya (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
Inventory to transport transition was a critical operation that requires high efficiency in manufacturing. This study models the inventory transition of manufacturing plants in a supply chain network. The objective was to configure the minimum fleet utilization with fastest waiting time.Â Â The configuration was performed using reinforcement learning assisted agent-based model (ABM) simulation. The ABM with fleet speed control have the best performance with average waiting time of 5.84 hours with lowest fleet utilization which surpasses other models. Lower fleet and waiting time provide rest periods for the driver. Therefore, performing speed control during transport improves human factor of the supply chain operation.